Relationship Between Mortality and Seizures After Intracerebral Hemorrhage: A Systematic Review and Meta-Analysis - Lin, Hong-yu; Wei, Qing-qing; Huang, Jian-yi; Pan, Xing-hua; Liang, Ning-chao; Huang, Cai-xia; Long, Teng; Gao, Wen; Shi, Sheng-liang (Frontiers in Neurology, 2022)
Background The relationship between mortality and seizures after intracerebral hemorrhage (ICH) has not yet been understood until now. A meta-analysis was performed to assess the effect of post-ICH seizures on mortality among patients with ICH. Methods PubMed and Embase were searched from the establishment of the databases to December 2021 to identify literature that evaluated the relationship between post-ICH seizures and mortality in ICH. Crude odds ratios and adjusted odds ratios with a 95% confidence interval (CI) were pooled using a random-effects model. Results Thirteen studies involving 245,908 participants were eventually included for analysis. The pooled estimate suggested that post-ICH seizures were not associated with significantly increased mortality in patients with ICH (crude odds ratios 1.35, 95% CI: 0.91–2; adjusted adds ratios 1.22, 95% CI: 0.78–1.88). However, the relationship was not consistent in subgroup analysis or robust in a sensitivity analysis. Conclusions This meta-analysis proved that post-ICH seizures were not associated with significantly increased mortality in patients with ICH. However, this result could be influenced by confounding factors, so more high-quality research is needed.